The Effect of Thinking Acceleration Model (CASE) on the Achievement of Mathematics and the Development of Self-confidence among Third-grade Intermediate Students - Ahmed Quaba, Shaymaa Hikmat (Journal of Tikrit University for Humanities, 2023)
The objective of this study is to examine the effects of the accelerated thinking model (CASE) on the academic performance in mathematics and the enhancement of self-confidence among female students in the third intermediate grade. In order to accomplish the objective of the study, three null hypotheses were created. The study included the deliberate selection of a sample of students from the third intermediate grade at Awat Secondary School for Girls during the academic year (2022-2023). The sample consisted of 61 students who were separated into two divisions. A cohort of 31 students was assigned to the experimental group, where they were exposed to the Acceleration Thinking Model. In contrast, a separate group of 30 students followed the conventional instructional approach. The study required the use of two instruments. The first assessment comprises a set of ten tasks designed to measure achievement. The exam was distinguished by its focus on honesty and stability. Additionally, the second measure of self-confidence, developed by AL Bayatl (2006), consisted of a set of 44 pre-determined questions. The pre-test for the self-confidence measure was administered to the student participants of the study sample on Sunday, February 26, 2023.The experiment was conducted from Monday, February 27, 2023, through Monday, March 27, 2023. The score test was conducted on Tuesday, March 28, 2023, while the post-confidence measure was administered on Wednesday, March 29, 2023. Data collection and analysis were performed using the Statistical Package for the Social Sciences (SPSS). The findings indicated that the experimental group shown significant improvements in both academic accomplishment and the growth of self-confidence. Additionally, the mean difference between the pre-test and post-test scores for self-confidence favoured the post-test, suggesting a positive impact of the intervention. The paper proposes the inclusion of conclusions, recommendations, and proposals.